Differentiation in the Quality of the Financial Audit Service in Mexico - Toscano Moctezuma, Juan Alfonso; Benau (Advances in Social Sciences Research Journal, 2016)
The objective of this paper of investigation tries to demonstrate empirically the reason that the existence of a high concentration in the market for financial auditing services in Mexico can be explained by the hypothesis of differentiation in the quality of service, concluding that the election of an auditor with reputation may be a determining factor of decision for certain companies that demand financial audit services with a quality that is higher than the legally required by auditing standards, a high quality of the service which provides accuracy, certainty and credibility on its financial statements and that is perceptible by third party interested users.